Poligami dan Sanksinya Menurut Perundang-undangan Negara-negara Modern. - Muhibbuthabry Muhibbuthabry (AHKAM : Jurnal Ilmu Syariah, 2016)
One of the interesting themes of Islamic family law reform is the legal status of polygamy. Almost all Muslim countries make efforts to narrow the space for the practice of polygamy by providing sanctions for the doers, including Tunisia, Pakistan, Egypt, Syria, Malaysia, and Indonesia. This article tries to discuss and analyze this case by making a comparison between the laws of family law in some countries—such as Tunisia, Pakistan, Egypt, Syria, Malaysia, and Indonesia—and the concept of classical fiqh. The study shows that even though each of these countries has the same spirit of renewal, they practice different reform issues related to polygamy. It can be clearly seen in the diversity of forms of sanctions for the doers of polygamy.DOI: 10.15408/ajis.v16i1.2891